2022
DOI: 10.1007/s10433-022-00701-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sociodemographic factors and close relatives at hospital discharge and post hospital care of older people with complex care needs: nurses’ perceptions on health inequity in three Nordic cities

Abstract: Hospital discharge of older people in need of both medical and social care following their hospital stay requires extensive coordination. This study aims to examine and compare the views of nurses in three Nordic cities on the influence of sociodemographic factors and having close relatives, for the hospital discharge and post hospital care of older people with complex health and social care needs. Thirty-five semi-structured interviews (Copenhagen n = 11, Tampere n = 8, Stockholm n = 16) with nurses were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These changes are partly driven by the rapidly ageing population, with high demand for health and social care, a major challenge that Finland shares with its Nordic neighbours [ 8 ]. Indeed, care coordination can facilitate the care to older people with complex health and social care needs [ 9 ]. Managing the responsibility for both health and social care at the same administrative level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are partly driven by the rapidly ageing population, with high demand for health and social care, a major challenge that Finland shares with its Nordic neighbours [ 8 ]. Indeed, care coordination can facilitate the care to older people with complex health and social care needs [ 9 ]. Managing the responsibility for both health and social care at the same administrative level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that bilingual healthcare workers as well as relatives are commonly used for translation in EDs and other healthcare settings instead of professional interpreters. [ 22 , 23 ] Using relatives for translation has however been found to be error-prone. [ 24 ] Further, the usage of relatives, especially younger children, can be problematic from both the carer perspective and relative perspective.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Further, the usage of relatives, especially younger children, can be problematic from both the carer perspective and relative perspective. [ 23 , 25 ] Patients not having access to an interpreter can also result in extensive mistakes. For instance, in a case in California, a healthy kidney was removed instead of the diseased one, as a patient underwent a nephrectomy after the patient signed a consent form in English and was not provided with an interpreter.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interview guide was developed based on previous research to address the research questions [1,8,30,31]. The interview guideline included questions on the health professionals' contributions, responsibilities, and influence on the discharge process.…”
Section: Design and Data Collectionmentioning
confidence: 99%